Effects of a lactobacillus salivarius probiotic intervention on infection, cold symptom duration and severity, and mucosal immunity in endurance athletes - Gleeson, M.; Bishop, N. C.; Oliveira, M.; McCauley, T.; Tauler, P.; Lawrence, C. (International Journal of Sport Nutrition and Exercise Metabolism, 2012)
The purpose of this study was to examine the effects of a probiotic supplement during 4 mo of spring training in men and women engaged in endurance-based physical activities on incidence of upper respiratory tract infections (URTI) and mucosal immune markers. Sixty-six highly active individuals were randomized to probiotic (n = 33) or placebo (n = 33) groups and, under double-blind procedures, received probiotic (PRO: Lactobacillus salivarius, 2 × 1010 bacterium colony-forming units) or placebo (PLA) daily for 16 wk. Resting blood and saliva samples were collected at baseline and after 8 and 16 wk. Weekly training and illness logs were kept. Fifty-four subjects completed the study (n = 27 PRO, n = 27 PLA). The proportion of subjects on PRO who experienced 1 or more wk with URTI symptoms was not different from that of those on PLA (PRO .58, PLA .59; p = .947). The number of URTI episodes was similar in the 2 groups (PRO 1.6 ± 0.3, PLA 1.4 ± 0.3; p = .710). Severity and duration of symptoms were not significantly different between treatments. Blood leukocyte, neutrophil, monocyte, and lymphocyte counts; saliva IgA; and lysozyme concentrations did not change over the course of the study and were not different on PRO compared with PLA. Regular ingestion of L. salivarius does not appear to be beneficial in reducing the frequency of URTI in an athletic cohort and does not affect blood leukocyte counts or levels of salivary antimicrobial proteins during a spring period of training and competition.